Correlation between Reading Strategy and Reading Comprehension of Class XI Students of SMA Negeri 3 Tambusai - Putri, Rizki Elvia; Niati , Batdal; Rasyidah , Ummi (Science, Technology and Education Care (STEDCA), 2025)
This study aims to determine the correlation between reading strategies and reading comprehension of eleventh-grade students at SMA Negeri 3 Tambusai. Thus, the research uses a correlational design. This research aims to determine whether there is a correlation between strategy and students' reading comprehension. The data obtained was taken from eleventh-grade students of SMA Negeri 3 Tambusai. The instruments used in collecting data were questionnaires and reading tests. The study population consisted of two classes. Researchers use a sample of two classes, which become non-experimental classes. The findings of this study are showing that the value of sig. (2-tailed) obtained is 0.049 < 0.05. No significant correlation exists between reading strategies and students' reading comprehension. Ha is rejected, and Ho is accepted. It can be seen from the data that the reading strategy has a high category in reading comprehension based on an average of 67.92 from the questionnaire results, 22.5% of which nine students are in the very high category. Finally, 75% of 30 students are in the high category, 2.5% of 1 student is in the low category, and the number of students is 40